A munkaerő-piaci előrejelzések nemzetközi gyakorlata -áttekintés a kvantitatív módszerekről és felhasználásukról - János Gács; Anikó Bíró (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
– The study was prepared in the framework of the "Priority Project TÁMOP - 2.3.2-09/1: Establishing labour market forecasts and foreseeing structural changes". It presents a comprehensive overview of labour market forecasting activities, mostly quantitative, based on multi-sector models, in 12 countries and the European Union. The principal aim of this effort is to provide ideas, lessons and benchmarks for similar forecasting exercises in Hungary. After outlining the basic model of quantitative labour market forecasting the paper identifies the technical conditions of model building and model quantification, as well as the characteristic features of organising the forecasting work. This analysis is based on the forecasting activities in individual countries. In the following section the authors address the paths of improvement in the traditional forecasting model. Here the possibilities of substitution in terms of occupations and qualifications are discussed, as well as their integration to the forecasting model. Another innovation is the inclusion of generic skills as a new variable in the forecasts. The next section deals with the analytical tools that can be used after the forecasts are ready, such as the shift-share analysis and the Indicator of Future Labour Market Situation (IFLM). The latter compares forecasted demand and supply in individual occupations or qualification categories. The discussion of forecasted labour shortages and vacancies as well as the measured accuracy of the forecasts leads us to one of the fundamental issues of labour market forecasts, i.e. whether the results of the calculations can be considered forecasts proper for future developments, or they should be seen simply as well-informed, systematic projections.
Keywords: E27; J11; J2; O41; 330; labour force requirement; labour supply; multi-sector models; forecasting; Arbeitsmarktprognose; Prognoseverfahren; Mehrsektoren-Modell